Literary Flourishing in TESOL: A Conceptual Framework for Wellbeing-Oriented Literature-Based EFL Pedagogy - Sunardi; Istanti Hermagustiana; Desy Rusmawaty; Noor Rachmawaty; Sirajuddin Kamal; Surjasni; Hengky (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: This conceptual review proposes Literary Flourishing in TESOL as an interdisciplinary framework for humanizing literature-based English language education. This article addresses the continued prevalence of instrumental TESOL paradigms, where literature is frequently relegated to supplementary reading, cultural content, or a means of vocabulary and comprehension practice. The article develops a conceptual model that positions literary engagement as a catalyst for human flourishing and linguistic development, drawing on a range of disciplines including positive psychology, wellbeing education, and narrative theory. Methodology: The proposed PERMA-LIGHT model expands on the PERMA dimensions of wellbeing, which include positive emotion, engagement, relationships, meaning, and accomplishment, by incorporating literary, humanistic, and transformative dimensions such as literary empathy, identity formation, global and intercultural understanding, humanistic growth, and transformative reflection. The article also outlines WOLBEP, or Wellbeing-Oriented Literature-Based EFL Pedagogy, as a pedagogical framework comprising emotional engagement, narrative immersion, reflective meaning-making, dialogic interaction, transformative response, and flourishing reflection. Findings: The review asserts that literature-based TESOL can foster linguistic competence, emotional wellbeing, empathy, identity formation, resilience, intercultural understanding, and reflective agency. The article provides a model for curriculum design, literature-based pedagogy, teacher education, and future research on language education that fosters flourishing. Conclusion: The review concludes that literature-based TESOL should be repositioned from a supplementary language resource to a wellbeing-oriented pedagogy that develops linguistic competence alongside empathy, identity formation, intercultural understanding, and reflective growth. Originality: The originality of this article lies in proposing Literary Flourishing in TESOL and operationalising it through the PERMA-LIGHT model and WOLBEP framework, which integrate wellbeing, literary pedagogy, and transformative learning into a unified conceptual approach.